Telemedicine for the Management of Glycemic Control and Clinical Outcomes of Type 1 Diabetes Mellitus: A Systematic Review and Meta-Analysis of Randomized Controlled Studies - Lee, Shaun W. H.; Ooi, Leanne; Lai, Yin K. (Frontiers in Pharmacology, 2017)
Importance: Telemedicine has been shown to be an efficient and effective means of providing care to patients with chronic disease especially in remote and undeserved regions, by improving access to care and reduce healthcare cost. However, the evidence surrounding its applicability in type 1 diabetes remains scarce and conflicting. Objective: To synthesize evidence and quantify the effectiveness of telemedicine interventions for the management of glycemic and clinical outcomes in type 1 diabetes patients, relative to comparator conditions Data Sources: MEDLINE, EMBASE, Cochrane Library, Web of Science, PsycINFO and CINAHL were searched for published articles since inception until December 2016. Study Selection: Original articles reporting the results of randomised controlled studies on the effectiveness of telemedicine in people with type 1 diabetes were included. Data Extraction and Synthesis: Two reviewers independently extracted data, assessed quality and strength of evidence. Interventions were categorized based upon the telemedicine focus (monitoring, education, consultation, case-management and peer mentoring). Main Outcome and Measure: Absolute change in glycosylated hemoglobin (HbA1c) from baseline to follow-up assessment. Results: A total of 38 studies described in 41 articles were identified. Positive effects on glycemic control were noted with studies examining telemedicine, with a mean reduction of 0.18% at the end of intervention. Studies with longer duration (>6 months) who had recruited patients with a higher baseline HbA1c (>9%) were associated with larger effects. Telemedicine interventions that involve individualised assessments, audit with feedback and skill building were also more effective in improving glycemic control. However, no benefits were observed on blood pressure, lipids, weight, quality of life and adverse events. Conclusions and Relevance: There is insufficient evidence to support telemedicine use for glycemic control and other clinically relevant outcome among patients with type 1 diabetes.